Análise computacional de sintases da quitina de fungos basidiomicetos - Diniz, Marcelo Vera Cruz (2010)
One of the main components of the fungal cell wall is the polysaccharide chitin, which is synthesized by the enzyme chitin synthase. Our work aimed to carry out an integrated in silico study of protein sequences of basidiomycotan chitin synthases using methods of comparative analysis of profiles and patterns, phylogenetic analyses, and complex network approach. Initially, we construct a relational database The following products were generated at the end of the project: (I) a relational database containing all complete or partial protein sequences of chitin syntases of Basidiomycota, constructed and validated; (II) identification and characterization of conserved domains of protein sequences; (III) phylogenetic trees of protein sequences; and (IV) complex networks protein sequences of basidiomycotan chitin synthases. The results will subsidize the development, by molecular modelling, of new compounds or chemical modifications of pré-existent compounds, addressed to the inhibition of the chitin synthesis in the cell wall of phytopathogenic Basidiomycota.